Escaping a POW camp - Summers, Jacque (Great escapes in history., 2019)
Offers four stories of successful escapes from prisoner of war camps during the Revolutionary War, the Civil War, World War II, and the Vietnam War. Includes photographs, a glossary, sidebars, critical thinking questions, and further resources.